Sitagliptin added to voglibose monotherapy improves glycemic control in patients with type 2 diabetes - Tajima, Naoko (Wiley-Blackwell, 2013)
AIMS/INTRODUCTION: Type 2 diabetes mellitus is a progressive disease that frequently requires patients to use more than one oral antihyperglycemic agent to achieve adequate glycemic control. The present multicenter, randomized study assessed the efficacy and safety of the addition of sitagliptin to ongoing voglibose monotherapy (0.2–0.3 mg three times daily) in Japanese patients with type 2 diabetes mellitus who had inadequate glycemic control (glycated hemoglobin ≥6.9% and <10.5%). MATERIALS AND METHODS: The present study had an initial 12‐week, double‐blind treatment period in which patients were randomized (1:1) to sitagliptin 50 mg/day (n = 70) or placebo (n = 63), followed by a 40‐week, open‐label treatment period during which all patients received sitagliptin 50 mg/day, that could have been increased to 100 mg/day for patients meeting predefined glycemic criteria. RESULTS: After 12 weeks, treatment with sitagliptin resulted in placebo‐subtracted mean changes from baseline in glycated hemoglobin (the primary end‐point), fasting plasma glucose and 2‐h postmeal glucose of –0.9%, –22.5 mg/dL and –51.3 mg/dL, respectively (all, P < 0.001). During the double‐blind period, adverse experiences were reported with similar frequency in both treatment groups, and the occurrences of hypoglycemia and gastrointestinal adverse experiences were low. In the open‐label period, sustained improvements in glycemic parameters were observed with sitagliptin treatment, and sitagliptin was generally well tolerated. CONCLUSIONS: Sitagliptin added on to ongoing voglibose monotherapy provided significant improvements in glycemic parameters and was well tolerated in Japanese patients with type 2 diabetes mellitus who had inadequate glycemic control. This trial was registered with ClinicalTrails.gov (no. NCT00837577).